Validation of the North American Chest Pain Rule in Prediction of Very Low-Risk Chest Pain; a Diagnostic Accuracy Study - Valadkhani, Somayeh; Jalili, Mohammad; Hesari, Elham; Mirfazaelian, Hadi (Archives of Academic Emergency Medicine, 2017)
Introduction: Acute coronary syndrome accounts for more than 15% of the chest pains. Recently, Hess et al. developed North American Chest Pain Rule (NACPR) to identify very low-risk patients who can be safely discharged from emergency department (ED). The present study aimed to validate this rule in EDs of two academic hospitals. Methods: A prospective diagnostic accuracy study was conducted on consecutive patients 24 years of age and older presenting to the ED with the chief complaint of acute chest pain, during March 2013 to June 2013. Chest pain characteristics, cardiac history, electrocardiogram findings, and cardiac biomarker measurement of patients were collected and screening performance characteristics of NACPR with 95% confidence interval were calculated using SPSS 21. Results: From 400 eligible patients with completed follow up, 69 (17.25 %) developed myocardial infarction, 121 (30.25%) underwent coronary revascularization, and 4 (2%) died because of cardiac or unidentifiable causes. By using NACPR, 34 (8.50%) of all the patients could be considered very low- risk and discharged after a brief ED assessment. Among these patients, none developed above-mentioned adverse outcomes within 30 days. Sensitivity, specificity, positive prediction value, and negative prediction value of the rule were 100% (95% CI: 87.35 - 100.00), 45.35 (95% CI: 40.19 - 50.61), 14.52 (95% CI: 10.40 – 19.85), and 100 (95% CI: 97.18 - 100.00), respectively. Conclusions: The present multicenter study showed that NACPR is a good screening tool for early discharge of patients with very low-risk chest pain from ED.